Hubungan Prilaku Remaja Berinternet di Inderalaya - Reza Firsandaya Malik; Deris Stiawan; Erwin Erwin; Rossi Passarella; sutarno sutarno; Sarmayanta Sembiring; Ahmad Heryanto (Annual Research Seminar (ARS), 2015)
Indralaya known as the City of Students and Education, also has more than 30 boarding school, and 60 senior high school / vocational school spread over Ogan Ilir. Implementation of community service performed in Inderalaya to determine the relationship of the behavior of teenagers surfs the internet and provide knowledge about healthy and safe while surfing an internet. The method of data collection using questionnaires. Number of questionnaires distributed as many as 27 participants from SMAN 1 Inderalaya Utara and Pondok Pesantren Al Ittifaqiyah based on age from 15 to 17 years. Results showed teenagers have the tendency to access the internet every day with a duration of 1-2 hours and mostly done in the bedroom. Applications often they use is social networking. The teens also have the courage to meet with people who are known via online with a percentage of 29.6%.